Excessive smartphone use in Tibet Autonomous Region: biopsychosocial and health behavior factors - Zhao, Ruixue; Yongzhulacuo,; Li, Zhaoyu; Nicholas, Stephen; Maitland, Elizabeth; Zhaxidawa,; Wang, Wenhua (Frontiers in Psychiatry, 2025)
BackgroundsExcessive smartphone use is a growing global health concern, with most research focusing on adolescents. Across all age groups, we assess the impact of regional, biopsychosocial and health behavior factors on excessive smartphone use in a unique ethnic group, Tibetans, in China.MethodsThrough systematic random sampling, we conducted a cross-sectional survey using the Mobile Phone Smartphone use Questionnaire (MPIQ) among 1,374 Tibetan residents from Shannan, Nyingchi, and Qamdo regions (October-December 2023). Data analysis included descriptive statistics, chi-square tests, one-way ANOVA, and multinomial logistic regression within a biopsychosocial framework.ResultsAmong the 1374 respondents, 30.28% were excessive smartphone users, with high excessive use rates across all age groups, including 20–39 young adults (40.53%), 40–65 middle-aged (26.86%) and over 65 (21.23%) aged groups. Significant regional disparities showed higher use in Qamdo and Nyingchi than in Shannan region. Males and individuals with higher depression scores (measured by the PHQ-9) more prone to excessive smartphone use, while regular physical exercise emerged as a protective factor. Socioeconomic factors, including education level, income level and water source, played a significant role in excessive smartphone use.ConclusionWith nearly one-third of the Tibetan sample excessively engaged in smartphone use, targeted and multifaceted public health interventions are essential. Interventions should holistically address both mental and physical health by integrating depression support and vigorously promoting physical activity. Furthermore, strategies must be tailored for key demographics, recognizing the risks facing young and middle-aged adults, men, and high-socioeconomic-status individuals. Finally, to ensure cultural resonance and effectiveness, interventions should leverage Tibet’s strong community ties by promoting traditional face-to-face interactions and be adapted to significant regional differences.